Lending standards and macroeconomic dynamics - Pedro Gete (European Central Bank (ECB), 2018)
This paper proposes a tractable way to incorporate lending standards ("credit qualification thresholds") into macro models of financial frictions. Banks can reject borrowers whose risk is above an endogenous threshold at which no lending rate sufficiently compensates banks for the borrowers' default risk. Firms denied credit cut employment and labor reallocates mostly towards safer producers. Lending standards propagate bank capital shortfalls through labor misallocation causing deeper and more persistent real effects. The paper also shows that lending spreads are insufficient indicators of credit supply disruptions. That is, for the same increase in credit spreads, output falls faster when denial rates are increasing. Finally, with endogenous lending standards, first-moment bank capital shocks look like second-moment shocks.
Keywords: E32; E44; E47; G2; 330; Bank Capital; Extensive Margin; Lending Standards; Labor Reallocation; Misallocation